Analisis Performa Waktu Eksekusi dan Penggunaan Memori Algoritma Linear Search dan Binary Search pada Sistem Pencarian Buku Perpustakaan Digital - Husnul Amisyah; Agung Kharisma Hidayah (Journal of Information System Research (JOSH), 2026)
The growth of digital libraries has increased the need for book search systems capable of providing fast and efficient retrieval as the amount of stored data continues to grow. Although Linear Search and Binary Search algorithms have been widely applied in search processes, their implementation and performance evaluation in web-based digital library systems still require analysis under practical implementation conditions. This study aims to analyze and compare the performance of both algorithms based on execution time and memory usage in a digital library book search system. An experimental method was employed by implementing Linear Search and Binary Search using PHP and MySQL. Performance testing was conducted on datasets containing 10, 50, 100, 500, and 1000 book records under the same testing environment. The results indicate that Binary Search achieved lower execution times for most dataset sizes; however, its execution time was slightly higher than Linear Search when tested with 1000 records. The average memory usage of Linear Search was 0.000048 MB, while Binary Search averaged 0.000043 MB, although Binary Search consumed more memory on the 500- and 1000-record datasets. These findings demonstrate that algorithm performance is influenced not only by theoretical complexity but also by system implementation, data characteristics, and the testing environment. Therefore, selecting a search algorithm should consider the implementation context and system requirements to achieve optimal performance.